High hardness aluminum bronze material and preparation method thereof
By precisely controlling the element content and surface laser cladding treatment in aluminum bronze materials, a gradient modification layer is formed, which solves the shortcomings of aluminum bronze materials in terms of high hardness and wear resistance, achieving high hardness and excellent wear resistance, and making it suitable for multiple industrial fields.
Patent Information
- Application Number
- CN202510561342.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-30
- Publication Date
- 2025-11-21
- Estimated Expiration
- 2045-04-30
AI Technical Summary
Existing aluminum bronze materials have shortcomings in terms of high hardness and wear resistance, especially in high loads and harsh environments where they are prone to wear, making it difficult to achieve high hardness while ensuring toughness and plasticity.
By precisely controlling the content and ratio of various elements in aluminum bronze materials, and applying magnetic field-assisted laser cladding of base material and wear-resistant material to its surface, a gradient modification layer is formed. Combined with tempering treatment, the microstructure is refined, and the internal structure and performance of the material are improved.
It significantly improves the hardness and plasticity of aluminum bronze materials, enhances wear resistance, extends service life, and maintains excellent performance under high impact and high friction environments.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of aluminum bronze material technology, specifically to a high-hardness aluminum bronze material and its preparation method. Background Technology
[0002] Aluminum bronze is an alloy material based on copper, with added aluminum and other elements (such as iron and nickel). Due to its excellent mechanical properties, good corrosion resistance, and high wear resistance, it is widely used in marine engineering, aerospace, chemical equipment, and mechanical engineering. With the continuous development of industrial technology, the performance requirements for aluminum bronze materials are constantly increasing, especially in applications requiring high hardness and high wear resistance, necessitating the development of high-hardness aluminum bronze materials with superior performance.
[0003] In the traditional production process of aluminum bronze, its hardness and strength can be improved to some extent by adjusting the aluminum content and controlling the heat treatment process. Although the aluminum content of aluminum bronze can affect its hardness, excessively high aluminum content will lead to increased brittleness, thereby affecting its processing performance and service life. Therefore, it is difficult to achieve high hardness while ensuring good toughness and plasticity. Although aluminum bronze itself has good wear resistance, its wear resistance is still insufficient under high loads and harsh environmental conditions, making it prone to wear and failure, which limits its use in high-performance applications.
[0004] Therefore, we propose a high-hardness aluminum bronze material and its preparation method. Summary of the Invention
[0005] The purpose of this invention is to provide a high-hardness aluminum bronze material and its preparation method to solve the problems raised in the prior art.
[0006] To achieve the above objectives, the present invention provides the following technical solution:
[0007] A method for preparing a high-hardness aluminum bronze material includes the following steps:
[0008] Step S1: Put the raw materials into a vacuum induction melting furnace and melt them at 1250-1350℃ to obtain an alloy liquid; continuously cast the alloy liquid at 1150-1300℃ to obtain an ingot; extrude the ingot to obtain aluminum bronze material.
[0009] Step S2: After grinding, polishing, cleaning and drying the aluminum bronze material, the base material is applied to the dried aluminum bronze material by magnetic field-assisted laser cladding in a synchronous powder feeding manner to obtain the base layer.
[0010] Step S3: The wear-resistant material is simultaneously fed into the base layer and subjected to magnetic field-assisted laser cladding to obtain a wear-resistant layer. Then, it is tempered to obtain a high-hardness aluminum bronze material.
[0011] Further, the raw material comprises the following components by mass percentage: 8-10% aluminum, 3-5% nickel, 1.5-2.5% chromium, 2-4% iron, 1-2% manganese, 0.1-0.5% niobium, 0.05-0.20% titanium, with the balance being copper.
[0012] Furthermore, the extrusion temperature is 700-800℃, and the extrusion ratio is 150-350.
[0013] Furthermore, the preparation method of the base material is as follows:
[0014] Nickel powder, chromium powder, silicon powder, magnetic graphene oxide, and iron powder are mixed evenly, ball-milled, and passed through a 200-mesh sieve to obtain the base material.
[0015] Furthermore, the base material is composed of the following components by mass percentage: 60-80% nickel, 8-12% chromium, 0.5-1.0% silicon, 0.3-0.5% magnetic graphene oxide, with the balance being iron.
[0016] Furthermore, the preparation method of the magnetic graphene oxide is as follows:
[0017] Graphene oxide and deionized water were mixed and ultrasonically dispersed for 1-2 hours to obtain a graphene oxide dispersion. A mixed solution of ferric nitrate nonahydrate, cobalt nitrate hexahydrate, and deionized water was added dropwise over 30-50 minutes. The pH was adjusted to 12.5-13.0 using sodium hydroxide solution. The mixture was then transferred to a hydrothermal reactor and reacted at 100°C for 22-24 hours. After centrifugation, washing, and drying, magnetic graphene oxide was obtained.
[0018] Furthermore, the concentration of the graphene oxide dispersion is 2 mg / mL.
[0019] Furthermore, the mass ratio of the graphene oxide to ferric nitrate nonahydrate is 1:(2-3).
[0020] Furthermore, the mass ratio of the nonahydrate ferric nitrate, the cobalt nitrate hexahydrate, and the deionized water is 1:(0.35-0.40):(20-30).
[0021] Furthermore, the preparation method of the wear-resistant material is as follows:
[0022] Nickel powder, modified boron nitride, tungsten carbide powder, chromium powder, silicon powder, carbon powder, and iron powder are mixed evenly, ball-milled, and passed through a 200-mesh sieve to obtain a wear-resistant material.
[0023] Furthermore, the wear-resistant material is composed of the following components by mass percentage: 10-15% nickel, 0.1-0.3% modified boron nitride, 0.5-1.0% tungsten carbide, 25-28% chromium, 0.5-1.0% silicon, 0.3-0.5% carbon, with the balance being iron.
[0024] Furthermore, the method for preparing the modified boron nitride is as follows:
[0025] Boron nitride was subjected to roughening, sensitization, activation and reduction pretreatment, then added to the plating solution for electroless nickel plating, vacuum filtration and cleaning, and drying to obtain modified boron nitride.
[0026] Furthermore, the roughening is performed using a 10wt% dilute nitric acid solution; the roughening time is 10-30 min.
[0027] Furthermore, the sensitizing solution used for sensitization comprises: 10-20 g / L stannous chloride and 20-50 mL / L hydrochloric acid; the sensitization time is 3-5 min.
[0028] Furthermore, the components of the activation solution are: palladium chloride 0.1-0.25 g / L, hydrochloric acid 2-5 mL / L; the activation time is 4-6 min.
[0029] Furthermore, the concentration of the hydrochloric acid is 1.19 g / L.
[0030] Furthermore, the reducing solution used for reduction is sodium hypophosphite with a concentration of 30 g / L, and the reduction time is 2-4 min.
[0031] Furthermore, the plating solution comprises: nickel sulfate hexahydrate 25-30 g / L, sodium hypophosphite 20-35 g / L, anhydrous sodium acetate 20-30 g / L, sodium citrate 10-20 g / L, and magnetic graphene oxide 2-8 g / L; the pH value of the plating solution is 4-5.
[0032] Furthermore, the electroless nickel plating process conditions are: temperature 65-85℃, time 10-30min.
[0033] Furthermore, the magnetic field-assisted laser cladding process conditions are as follows: laser power 2000-3000W, scanning speed 3-5mm / s, spot diameter 2-5mm, argon flow rate 15-18L / min, magnetic field strength 10-30T, and powder feeding speed 1.5-3.0g / s.
[0034] Furthermore, the ball milling process conditions are as follows: ball-to-material ratio of (5-8):1, ball milling for 2-4 hours, ball milling speed of 200-300 rpm, and grinding balls made of stainless steel.
[0035] Furthermore, in step S3, the tempering process conditions are as follows: first, hold at 400-440℃ for 1-2 hours, then hold at 460-500℃ for 3-4 hours, followed by air cooling.
[0036] Furthermore, the thickness of the underlayer is 0.2-0.4 mm, and the thickness of the wear-resistant layer is 0.5-2.0 mm.
[0037] Compared with the prior art, the beneficial effects of the present invention are:
[0038] This invention discloses a high-hardness aluminum bronze material and its preparation method. By precisely controlling the content and ratio of various elements in the aluminum bronze material, the hardness and plasticity of the material are significantly improved while ensuring high strength, thus giving the aluminum bronze material excellent comprehensive performance. Among them, Al element strengthens the matrix, Ni and Cr elements improve corrosion resistance and high temperature stability, and Nb and Ti refine the grains and inhibit the precipitation of brittle phases.
[0039] Based on this scheme, this application achieves gradient modification of the substrate material by laser cladding the base material and then sequentially laser-cladding the base material and wear-resistant material. Tempering is then performed to eliminate residual stress in the cladding layer, improve the stability of the material's internal structure and performance, and further enhance its hardness. In this scheme, a base material is first formed by ball milling a mixture of nickel powder, chromium powder, silicon powder, magnetic graphene oxide, and iron powder. The introduction of magnetic graphene oxide, combined with an external magnetic field, significantly refines the microstructure, improves the uniformity of the structure, and effectively eliminates common porosity and crack defects in traditional laser cladding layers, thereby improving the product's wear resistance. Next, a wear-resistant material is obtained by ball milling a mixture of nickel powder, modified boron nitride, tungsten carbide powder, chromium powder, silicon powder, carbon powder, and iron powder. Modified boron nitride is chemically plated to prepare magnetic graphene oxide-nickel composite coatings with varying contents, solving the problem of poor interfacial bonding between boron nitride and the metal substrate. Meanwhile, the modified boron nitride and tungsten carbide work synergistically to improve the overall stability and wear resistance of the wear-resistant material. This not only extends the service life of the aluminum bronze material, but also maintains good performance under high impact and high friction environments, achieving superior wear resistance and strength. Detailed Implementation
[0040] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0041] In this embodiment, the graphene oxide was provided by Xianfeng Nano, model XF002-2; the boron nitride was hexagonal boron nitride, provided by Jiangsu Xianfeng Nano, model XFBN03-1; the nickel powder was provided by Bohuas Nanotechnology, model Brofos-Ni; the chromium powder was provided by Bohuas Nanotechnology, model Brofos-Cr; the silicon powder was provided by Aladdin, model S108981; the iron powder was provided by Bohuas Nanotechnology, model Brofos-Fe; and the tungsten carbide powder was provided by Xianfeng Nano, model XFI51.
[0042] Unless otherwise specified, all the following quantities are parts by weight.
[0043] Example 1: A method for preparing a high-hardness aluminum bronze material, comprising the following processes:
[0044] Step S1: Put the raw materials into a vacuum induction melting furnace and melt them at 1250°C to obtain an alloy liquid; continuously cast the alloy liquid at 1150°C to obtain an ingot; extrude the ingot to form an aluminum bronze material at a temperature of 700°C and an extrusion ratio of 150.
[0045] Step S2: Mix nickel powder, chromium powder, silicon powder, magnetic graphene oxide and iron powder evenly, ball mill, and pass through a 200-mesh sieve to obtain the base material; the base material is composed of the following components by mass percentage: nickel 60%, chromium 8%, silicon 0.5%, magnetic graphene oxide 0.3%, and the balance is iron;
[0046] After grinding, polishing, cleaning and drying the aluminum bronze material, the base material is applied to the dried aluminum bronze material by magnetic field-assisted laser cladding in a synchronous powder feeding manner to obtain the base layer.
[0047] Step S3: Mix nickel powder, modified boron nitride, tungsten carbide powder, chromium powder, silicon powder, carbon powder and iron powder evenly, ball mill, and pass through a 200-mesh sieve to obtain a wear-resistant material; the wear-resistant material is composed of the following components by mass percentage: nickel 10%, modified boron nitride 0.1%, tungsten carbide 0.5%, chromium 25%, silicon 0.5%, carbon 0.3%, and the balance is iron;
[0048] Wear-resistant material was simultaneously fed into the substrate and subjected to magnetic field-assisted laser cladding to obtain a wear-resistant layer. The substrate was then tempered, first held at 400℃ for 1 hour, then at 460℃ for 3 hours, and finally air-cooled to obtain a high-hardness aluminum bronze material. The substrate thickness was 0.3 mm, and the wear-resistant layer thickness was 1 mm. The magnetic field-assisted laser cladding process conditions were: laser power 2000 W, scanning speed 3 mm / s, spot diameter 2 mm, argon flow rate 15 L / min, magnetic field strength 10 T, and powder feeding speed 1.5 g / s. The ball milling process conditions were: ball-to-material ratio 5:1, ball milling for 2 hours, ball milling speed 200 rpm, and stainless steel grinding balls.
[0049] The raw materials consist of the following components by weight percentage: aluminum 8%, nickel 3%, chromium 1.5%, iron 2%, manganese 1%, niobium 0.1%, titanium 0.05%, with the balance being copper;
[0050] The preparation method of magnetic graphene oxide is as follows:
[0051] Graphene oxide and deionized water were mixed and ultrasonically dispersed for 1 hour to obtain a 2 mg / mL graphene oxide dispersion. A mixed solution of ferric nitrate nonahydrate, cobalt nitrate hexahydrate, and deionized water was added dropwise over 30 minutes. The pH was adjusted to 13.0 using sodium hydroxide solution. The mixture was then transferred to a hydrothermal reactor and reacted at 100°C for 22 hours. After centrifugation, washing, and drying, magnetic graphene oxide was obtained. The mass ratio of graphene oxide to ferric nitrate nonahydrate was 1:2; the mass ratio of ferric nitrate nonahydrate, cobalt nitrate hexahydrate, and deionized water was 1:0.35:20.
[0052] The preparation method of modified boron nitride is as follows:
[0053] Boron nitride was roughened (using a 10wt% dilute nitric acid solution) for 10 min, then sensitized (the sensitization solution consisted of 10 g / L stannous chloride and 20 mL / L 1.19 g / L hydrochloric acid) for 3 min, followed by vacuum filtration and cleaning. Then it was activated (the activation solution consisted of 0.1 g / L palladium chloride and 2 mL / L 1.19 g / L hydrochloric acid) for 4 min. After vacuum filtration and cleaning, it was reduced (using 30 g / L sodium hypophosphite) for 2 min, then vacuum filtration, cleaning, and drying. The resulting product was then added to a plating solution for electroless nickel plating at 65℃ for 30 min, followed by vacuum filtration, cleaning, and drying to obtain modified boron nitride. The plating solution consisted of 25 g / L nickel sulfate hexahydrate, 20 g / L sodium hypophosphite, 20 g / L anhydrous sodium acetate, 10 g / L sodium citrate, and 2 g / L magnetic graphene oxide. The pH of the plating solution was 4.
[0054] Example 2: A method for preparing a high-hardness aluminum bronze material, comprising the following processes:
[0055] Step S1: Put the raw materials into a vacuum induction melting furnace and melt them at 1300°C to obtain an alloy liquid; continuously cast the alloy liquid at 1200°C to obtain an ingot; extrude the ingot to form an aluminum bronze material at a temperature of 750°C and an extrusion ratio of 200.
[0056] Step S2: Mix nickel powder, chromium powder, silicon powder, magnetic graphene oxide and iron powder evenly, ball mill, and pass through a 200-mesh sieve to obtain the base material; the base material is composed of the following components by mass percentage: nickel 70%, chromium 10%, silicon 0.8%, magnetic graphene oxide 0.4%, and the balance is iron;
[0057] After grinding, polishing, cleaning and drying the aluminum bronze material, the base material is applied to the dried aluminum bronze material by magnetic field-assisted laser cladding in a synchronous powder feeding manner to obtain the base layer.
[0058] Step S3: Mix nickel powder, modified boron nitride, tungsten carbide powder, chromium powder, silicon powder, carbon powder and iron powder evenly, ball mill, and pass through a 200-mesh sieve to obtain a wear-resistant material; the wear-resistant material is composed of the following components by mass percentage: nickel 12%, modified boron nitride 0.2%, tungsten carbide 0.8%, chromium 27%, silicon 0.8%, carbon 0.4%, and the balance is iron;
[0059] Wear-resistant material was simultaneously fed into the substrate and subjected to magnetic field-assisted laser cladding to obtain a wear-resistant layer. The substrate was then tempered, first held at 420℃ for 1.5 hours, then at 480℃ for 3.5 hours, followed by air cooling to obtain a high-hardness aluminum bronze material. The substrate thickness was 0.3 mm, and the wear-resistant layer thickness was 1 mm. The magnetic field-assisted laser cladding process conditions were: laser power 2500 W, scanning speed 4 mm / s, spot diameter 3 mm, argon flow rate 16 L / min, magnetic field strength 20 T, and powder feeding speed 2 g / s. The ball milling process conditions were: ball-to-material ratio 6:1, ball milling for 3 hours, ball milling speed 250 rpm, and stainless steel grinding balls.
[0060] The raw materials consist of the following components by weight percentage: aluminum 9%, nickel 4%, chromium 2%, iron 3%, manganese 1.5%, niobium 0.3%, titanium 0.1%, with the balance being copper;
[0061] The preparation method of magnetic graphene oxide is as follows:
[0062] Graphene oxide and deionized water were mixed and ultrasonically dispersed for 1.5 h to obtain a 2 mg / mL graphene oxide dispersion. A mixed solution of ferric nitrate nonahydrate, cobalt nitrate hexahydrate, and deionized water was added dropwise over 40 min. The pH was adjusted to 12.8 using sodium hydroxide solution, and the mixture was transferred to a hydrothermal reactor and reacted at 100 °C for 23 h. After centrifugation, washing, and drying, magnetic graphene oxide was obtained. The mass ratio of graphene oxide to ferric nitrate nonahydrate was 1:2.5; the mass ratio of ferric nitrate nonahydrate, cobalt nitrate hexahydrate, and deionized water was 1:0.38:25.
[0063] The preparation method of modified boron nitride is as follows:
[0064] Boron nitride was roughened (using 10wt% dilute nitric acid solution) for 20 min, followed by vacuum filtration and sensitization (sensitization solution consisted of 15 g / L stannous chloride and 40 mL / L 1.19 g / L hydrochloric acid) for 4 min. After vacuum filtration and washing, it was activated (activation solution consisted of 0.2 g / L palladium chloride and 3 mL / L 1.19 g / L hydrochloric acid) for 5 min. After vacuum filtration and washing, it was reduced... The original solution (reducing solution is 30 g / L sodium hypophosphite) was reduced for 3 min. After vacuum filtration and cleaning, and drying, it was added to the plating solution for electroless nickel plating. It was immersed at 75℃ for 20 min, vacuum filtration and cleaning, and drying to obtain modified boron nitride. The components of the plating solution were: nickel sulfate hexahydrate 28 g / L, sodium hypophosphite 25 g / L, anhydrous sodium acetate 25 g / L, sodium citrate 15 g / L, and magnetic graphene oxide 6 g / L. The pH value of the plating solution was 4.5.
[0065] Example 3: A method for preparing a high-hardness aluminum bronze material, comprising the following processes:
[0066] Step S1: Put the raw materials into a vacuum induction melting furnace and melt them at 1350°C to obtain an alloy liquid; continuously cast the alloy liquid at 1300°C to obtain an ingot; extrude the ingot to form an aluminum bronze material at a temperature of 800°C and an extrusion ratio of 350.
[0067] Step S2: Mix nickel powder, chromium powder, silicon powder, magnetic graphene oxide and iron powder evenly, ball mill, and pass through a 200-mesh sieve to obtain the base material; the base material is composed of the following components by mass percentage: nickel 80%, chromium 12%, silicon 1.0%, magnetic graphene oxide 0.5%, and the balance is iron;
[0068] After grinding, polishing, cleaning and drying the aluminum bronze material, the base material is applied to the dried aluminum bronze material by magnetic field-assisted laser cladding in a synchronous powder feeding manner to obtain the base layer.
[0069] Step S3: Mix nickel powder, modified boron nitride, tungsten carbide powder, chromium powder, silicon powder, carbon powder, and iron powder evenly, ball mill, and pass through a 200-mesh sieve to obtain a wear-resistant material. The thickness of the base layer is 0.3 mm, and the thickness of the wear-resistant layer is 1 mm. The wear-resistant material is composed of the following components by mass percentage: nickel 15%, modified boron nitride 0.3%, tungsten carbide 1%, chromium 28%, silicon 1%, carbon 0.5%, and the balance is iron.
[0070] Wear-resistant material was simultaneously fed into the substrate and subjected to magnetic field-assisted laser cladding to obtain a wear-resistant layer. The layer was then tempered, first held at 440℃ for 2 hours, then at 500℃ for 4 hours, followed by air cooling to obtain high-hardness aluminum bronze material. The magnetic field-assisted laser cladding process conditions were: laser power 3000W, scanning speed 5mm / s, spot diameter 5mm, argon flow rate 18L / min, magnetic field strength 30T, and powder feeding speed 3.0g / s. The ball milling process conditions were: ball-to-material ratio 8:1, ball milling for 4 hours, ball milling speed 300rpm, and stainless steel grinding balls.
[0071] The raw materials consist of the following components by weight percentage: 10% aluminum, 5% nickel, 2.5% chromium, 4% iron, 2% manganese, 0.5% niobium, 0.20% titanium, with the balance being copper;
[0072] The preparation method of magnetic graphene oxide is as follows:
[0073] Graphene oxide and deionized water were mixed and ultrasonically dispersed for 2 hours to obtain a 2 mg / mL graphene oxide dispersion. A mixed solution of ferric nitrate nonahydrate, cobalt nitrate hexahydrate, and deionized water was added dropwise over 50 minutes. The pH was adjusted to 12.5 using sodium hydroxide solution. The mixture was then transferred to a hydrothermal reactor and reacted at 100°C for 24 hours. After centrifugation, washing, and drying, magnetic graphene oxide was obtained. The mass ratio of graphene oxide to ferric nitrate nonahydrate was 1:3; the mass ratio of ferric nitrate nonahydrate, cobalt nitrate hexahydrate, and deionized water was 1:0.4:30.
[0074] The preparation method of modified boron nitride is as follows:
[0075] Boron nitride was roughened (using a 10wt% dilute nitric acid solution) for 30 min, followed by vacuum filtration and sensitization (sensitization solution consisting of 20 g / L stannous chloride and 50 mL / L 1.19 g / L hydrochloric acid) for 5 min. After vacuum filtration and cleaning, it was activated (activation solution consisting of 0.25 g / L palladium chloride and 5 mL / L 1.19 g / L hydrochloric acid) for 6 min. After vacuum filtration and cleaning, it was reduced (reducing solution consisting of 30 g / L sodium hypophosphite) for 4 min. After vacuum filtration and cleaning and drying, it was added to a plating solution for electroless nickel plating at 85℃ for 10 min. After vacuum filtration and cleaning and drying, modified boron nitride was obtained. The plating solution consisted of 30 g / L nickel sulfate hexahydrate, 35 g / L sodium hypophosphite, 30 g / L anhydrous sodium acetate, 20 g / L sodium citrate, and 8 g / L magnetic graphene oxide. The pH of the plating solution was 5.
[0076] Comparative Example 1: A method for preparing a high-hardness aluminum bronze material, comprising the following processes:
[0077] Step S1: Put the raw materials into a vacuum induction melting furnace and melt them at 1350°C to obtain an alloy liquid; continuously cast the alloy liquid at 1300°C to obtain an ingot; extrude the ingot to form an aluminum bronze material at a temperature of 800°C and an extrusion ratio of 350.
[0078] Step S2: Mix nickel powder, modified boron nitride, tungsten carbide powder, chromium powder, silicon powder, carbon powder, and iron powder evenly, ball mill, and pass through a 200-mesh sieve to obtain a wear-resistant material. The thickness of the base layer is 0.3 mm, and the thickness of the wear-resistant layer is 1 mm. The wear-resistant material is composed of the following components by mass percentage: nickel 15%, modified boron nitride 0.3%, tungsten carbide 1%, chromium 28%, silicon 1%, carbon 0.5%, and the balance is iron.
[0079] After grinding, polishing, cleaning, and drying, wear-resistant material is simultaneously fed powder onto the dried aluminum bronze material and subjected to magnetic field-assisted laser cladding to obtain a wear-resistant layer. The material is then tempered, first held at 440℃ for 2 hours, then at 500℃ for 4 hours, and finally air-cooled to obtain high-hardness aluminum bronze material. The magnetic field-assisted laser cladding process conditions are as follows: laser power 3000W, scanning speed 5mm / s, spot diameter 5mm, argon flow rate 18L / min, magnetic field strength 30T, and powder feeding speed 3.0g / s. The ball milling process conditions are as follows: ball-to-material ratio 8:1, ball milling for 4 hours, ball milling speed 300rpm, and stainless steel grinding balls.
[0080] Example 3 was used as the control group. In Comparative Example 1, no underlying layer was introduced, and the other steps were the same as in Example 3.
[0081] Comparative Example 2: A method for preparing a high-hardness aluminum bronze material, comprising the following processes:
[0082] Example 3 was used as the control group. In Comparative Example 2, no magnetic field assistance was introduced, and the other steps were the same as in Example 3.
[0083] Comparative Example 3: A method for preparing a high-hardness aluminum bronze material, comprising the following processes:
[0084] Using Example 3 as the control group, Comparative Example 3 replaced the modified boron nitride with the same mass of boron nitride, and the other steps were the same as in Example 3.
[0085] Testing experiment:
[0086] 1. Take the high-hardness aluminum bronze material obtained in Examples 1-3 and Comparative Examples 1-3, prepare samples, and perform microhardness testing on the sample surface. The load is 1 kg, the holding time is 20 s, and test points at different locations 3-5 times, and take the average value.
[0087] 2. Take the high-hardness aluminum bronze materials obtained in Examples 1-3 and Comparative Examples 1-3, prepare samples, and use HSR-2M high-speed reciprocating friction wear tester to conduct wear resistance tests. The parameters are set as follows: reciprocating length 5mm, reciprocating frequency 500 times / min, load 620g, time 120min, and the paired friction pair is a hard ball of HV1050. Record the coefficient of friction.
[0088] Test Results
[0089]
[0090] Based on the data in the table above, the following conclusions can be clearly drawn:
[0091] Compared with Examples 1-3, the hardness and wear resistance of Comparative Examples 1-3 decreased, indicating that the present invention discloses a high-hardness aluminum bronze material and its preparation method. The process formula is reasonably designed, and the scheme involves irradiating the surface of the aluminum bronze material with magnetic field laser cladding to form an underlayer and a wear-resistant layer, which makes the product have excellent wear resistance and high hardness. It can be widely used in many industrial fields and has excellent practical prospects.
[0092] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.
Claims
1. A method for preparing a high-hardness aluminum bronze material, characterized in that: Includes the following steps: Step S1: Put the raw materials into a vacuum induction melting furnace and melt them at 1250-1350℃ to obtain an alloy liquid; continuously cast the alloy liquid at 1150-1300℃ to obtain an ingot; extrude the ingot to obtain aluminum bronze material. Step S2: After grinding, polishing, cleaning and drying the aluminum bronze material, the base material is applied to the dried aluminum bronze material by magnetic field-assisted laser cladding in a synchronous powder feeding manner to obtain the base layer. Step S3: The wear-resistant material is simultaneously fed into the base layer and subjected to magnetic field-assisted laser cladding to obtain a wear-resistant layer. Then, it is tempered to obtain a high-hardness aluminum bronze material. The base material is composed of the following components by mass percentage: 60-80% nickel, 8-12% chromium, 0.5-1.0% silicon, 0.3-0.5% magnetic graphene oxide, and the balance being iron; The wear-resistant material is composed of the following components by mass percentage: nickel 10-15%, modified boron nitride 0.1-0.3%, tungsten carbide 0.5-1.0%, chromium 25-28%, silicon 0.5-1.0%, carbon 0.3-0.5%, with the balance being iron; The method for preparing the modified boron nitride is as follows: Boron nitride was subjected to roughening, sensitization, activation and reduction pretreatment, then added to the plating solution for electroless nickel plating, vacuum filtration and cleaning, and drying to obtain modified boron nitride. The plating solution consists of: nickel sulfate hexahydrate 25-30 g / L, sodium hypophosphite 20-35 g / L, anhydrous sodium acetate 20-30 g / L, sodium citrate 10-20 g / L, and magnetic graphene oxide 2-8 g / L.
2. The method for preparing a high-hardness aluminum bronze material according to claim 1, characterized in that: The raw materials comprise the following components by mass percentage: 8-10% aluminum, 3-5% nickel, 1.5-2.5% chromium, 2-4% iron, 1-2% manganese, 0.1-0.5% niobium, 0.05-0.20% titanium, with the balance being copper.
3. The method for preparing a high-hardness aluminum bronze material according to claim 1, characterized in that: The preparation method of the base material is as follows: Nickel powder, chromium powder, silicon powder, magnetic graphene oxide, and iron powder are mixed evenly, ball-milled, and passed through a 200-mesh sieve to obtain the base material.
4. The method for preparing a high-hardness aluminum bronze material according to claim 1, characterized in that: The magnetic graphene oxide is prepared as follows: Graphene oxide and deionized water were mixed and ultrasonically dispersed for 1-2 hours to obtain a graphene oxide dispersion. A mixed solution of ferric nitrate nonahydrate, cobalt nitrate hexahydrate, and deionized water was added dropwise over 30-50 minutes. The pH was adjusted to 12.5-13.0 using sodium hydroxide solution. The mixture was then transferred to a hydrothermal reactor and reacted at 100°C for 22-24 hours. After centrifugation, washing, and drying, magnetic graphene oxide was obtained.
5. The method for preparing a high-hardness aluminum bronze material according to claim 1, characterized in that: The preparation method of the wear-resistant material is as follows: Nickel powder, modified boron nitride, tungsten carbide powder, chromium powder, silicon powder, carbon powder, and iron powder are mixed evenly, ball-milled, and passed through a 200-mesh sieve to obtain a wear-resistant material.
6. A high-hardness aluminum bronze material prepared by the preparation method according to any one of claims 1-5.
Citation Information
Patent Citations
Laser-cladding material and preparation method thereof, aluminum bronze base surface modification material and preparation method thereof
CN105420723A
Wear-resistant corrosion-resistant multi-element manganese-aluminum bronze brazing alloy and preparation method thereof
CN111074089A
Cited By
Preparation method of high-hardness wear-resistant aluminum bronze alloy
CN122256748A